The effect of steady and pulsed air jet vortex generator blowing on an aerofoil section model undergoing sinusoidal pitching - Prince, Simon A.; Green, Richard; Coton, Frank; Wang, Yaxing (Vertical Flight Society, 2019)
Experimental results are reported on the assessment of steady and pulsed air jet vortex generators (AJVGs) for the suppression of dynamic stall on a sinusoidal pitching RAE9645 airfoil model. Tests at Rec of 1 million, at reduced pitching frequencies between 0.01 and 0.10 were performed with and without steady and pulsed AJVG blowing. The effect of jet momentum coefficient (0.0003< C μ < 0.0046), jet duty cycle (0.25< DC< 1) and jet pulsing frequency (0.29< F +< 2.93) were investigated. Pulsed air jet blowing with F + in the range 0.5–1.0 and with a duty cycle in the range 0.4–0.5, was found to be the most effective to achieve full suppression of dynamic stall vortex formation.